Muscle glycogen utilisation during Rugby match play: Effects of pre-game carbohydrate - Bradley, W. J.; Morehen, J. C.; Haigh, J.; Clarke, J.; Donovan, T. F.; Twist, C.; Cotton, C.; Shepherd, S.; Cocks, M.; Sharma, A.; Impey, S. G.; Cooper, R. G.; et al. (Journal of Science and Medicine in Sport, 2016)
Objectives Although the physical demands of Rugby League (RL) match-play are well-known, the fuel sources supporting energy-production are poorly understood. We therefore assessed muscle glycogen utilisation and plasma metabolite responses to RL match-play after a relatively high (HCHO) or relatively low CHO (LCHO) diet. Design Sixteen (mean ± SD age; 18 ± 1 years, body-mass; 88 ± 12 kg, height 180 ± 8 cm) professional players completed a RL match after 36-h consuming a non-isocaloric high carbohydrate (n = 8; 6 g kg day-1) or low carbohydrate (n = 8; 3 g kg day-1) diet. Methods Muscle biopsies and blood samples were obtained pre- and post-match, alongside external and internal loads quantified using Global Positioning System technology and heart rate, respectively. Data were analysed using effects sizes ±90% CI and magnitude-based inferences. Results Differences in pre-match muscle glycogen between high and low carbohydrate conditions (449 ± 51 and 444 ± 81 mmol kg-1 d.w.) were unclear. High (243 ± 43 mmol kg-1 d.w.) and low carbohydrate groups (298 ± 130 mmol kg-1 d.w.) were most and very likely reduced post-match, respectively. For both groups, differences in pre-match NEFA and glycerol were unclear, with a most likely increase in NEFA and glycerol post-match. NEFA was likely lower in the high compared with low carbohydrate group post-match (0.95 ± 0.39 mmol l-1 and 1.45 ± 0.51 mmol l-1, respectively), whereas differences between the 2 groups for glycerol were unclear (98.1 ± 33.6 mmol l-1 and 123.1 ± 39.6 mmol l-1) in the high and low carbohydrate groups, respectively. Conclusions Professional RL players can utilise ~40% of their muscle glycogen during a competitive match regardless of their carbohydrate consumption in the preceding 36-h.